EVOLUTION OF THE RIGHT TO PRIVACY IN INDIA: CONSTITUTIONAL PERSPECTIVE AND JUDICIAL APPROACH - Kurlwal, Anupam; Shreyansh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India's journey toward recognizing the Right to Privacy is a remarkable constitutional achievement. Once entirely absent from the written Constitution and explicitly rejected by early courts as seen in cases like M.P. Sharma and Kharak Singh, privacy has now emerged as a cornerstone fundamental right. This paper lays down this profound transformation, driven significantly by judicial interpretation and activism. The paper explores how courts progressively reshaped the understanding of "life and personal liberty" under Article 21, culminating in the historic K.S. Puttaswamy verdict, which firmly anchored privacy within the Constitution as essential to human dignity, autonomy, and freedom. Beyond tracing this legal evolution, the paper delves into the philosophical bedrock of privacy. It examines its roots in natural rights theory and liberal constitutionalism, while also confronting the unique pressures of our digital age. Further, the paper analyses the pivotal Supreme Court rulings that built India's privacy jurisprudence and assess whether current laws, including the new Digital Personal Data Protection Act 2023, provide sufficient safeguards. Ultimately, the paper moves beyond diagnosis to propose concrete suggestions for strengthening the right to privacy for every individual in India.